2011
DOI: 10.1088/0004-637x/728/2/91
|View full text |Cite
|
Sign up to set email alerts
|

Infall and Outflow Detections in a Massive Core JCMT 18354–0649s

Abstract: We present a high-resolution study of a massive dense core JCMT 18354−0649S with the Submillimeter Array. The core is mapped with continuum emission at 1.3 mm and molecular lines including CH 3 OH (5 23 -4 13 ) and HCN (3-2). The dust core detected in the compact configuration has a mass of 47 M and a diameter of 2 (0.06 pc), which is further resolved into three condensations with a total mass of 42 M under higher spatial resolution. The HCN (3-2) line exhibits an asymmetric profile consistent with infall sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…Therefore, the study and characterization of the outflow and infall processes involved in the formation of high-mass stars need to be understood in more detail. Since high-mass stars form in dense cores, dense gas tracers such as HCN are useful in identifying outflow and infall motions (e. g., Liu et al 2011aLiu et al , 2011bLiu et al , 2013Liu et al , 2015Wu et al 2005). It has also been demonstrated that the profile of spectral lines such as and HCO + (3-2) are good tools to search for and study the infall motions (see simulations by Smith et al 2012Smith et al , 2013and Chira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study and characterization of the outflow and infall processes involved in the formation of high-mass stars need to be understood in more detail. Since high-mass stars form in dense cores, dense gas tracers such as HCN are useful in identifying outflow and infall motions (e. g., Liu et al 2011aLiu et al , 2011bLiu et al , 2013Liu et al , 2015Wu et al 2005). It has also been demonstrated that the profile of spectral lines such as and HCO + (3-2) are good tools to search for and study the infall motions (see simulations by Smith et al 2012Smith et al , 2013and Chira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Spectral line observations of high-density tracers, including HCN(3-2), HCO + (3-2), H 13 CO + (3-2), and C 17 O(2-1), reveal a prominent blue profile (Wu et al 2005), which was confirmed with the Submillimeter Array (SMA) observations (Liu et al 2011), indicating that this core is collapsing. In addition, at the full width zero intensity (FWZI) level the HCN(3-2) and CO(3-2) line profiles span 38 km s −1 (Wu et al 2005), indicating outflow motions in this region.…”
Section: Introductionmentioning
confidence: 54%
“…The extended taillike feature may be the partially resolved counterpart of IRS1b, judging from its IRAC color. However, we cannot completely rule out the existence of shocked gas surrounding the protostars, as outflows are clearly seen on the HCN(3-2) map from the SMA (Liu et al 2011). If part of the extended emissions are indeed from shocked gas, the measured fluxes at 4.5 μm (and possibly at 5.8 μm) should be used as upper limits.…”
Section: Source Multiplicity In the J18354s Corementioning
confidence: 95%
See 2 more Smart Citations